A 9th-Order Continuous Time Sigma-Delta-ADC with X-Coupled Differential Single-Opamp Resonators - Zeller, Sebastian; Münker, Christian; Weigel, Robert (IEEE International Midwest Symposium on Circuits and Systems, 2011)
Continuous time Sigma-Delta-ADCs are usually designed with noise transfer functions containing conjugate complex zeros to extend the usable bandwidth. Traditionally, these zeros are implemented with a resonance generated by feedback around two integrator opamps.
elib2cris::1512001600,zeller2011a
Keywords: continuous time systems; differential amplifiers; integrating circuits; operational amplifiers; poles and zeros; conjugate complex zeros